Asymptotic behavior of solutions to second-order differential equations with fractional derivative perturbations - Eva Brestovanska; Milan Medved (Electronic Journal of Differential Equations, 2014)
In this article we study the asymptotic behavior of solutions to nonlinear second-order differential equations having perturbations that involve Caputo's derivatives of several fractional orders. We find sufficient conditions for all solutions to be asymptotic to a straight line.